UMKM Creative Exhibition as a Realization of the Potential of the Rising Economic Village Desa Perkebunan Tanjung Kasau - Manalu, Sarah Patumona; Muharani, Aruni; Widyawati, Elisa; Nurzanna, Tasya Nabilla (Talenta Publisher, 2023)
Exhibitions are one of the communication channels for UMKM to meet customers directly, acquire new customers, establish communication and cooperation with business partners, improve their image and obtain information about competitors. Exhibitions are an important medium for UMKM to expand their market and make business contacts with customers and partners, which in turn is expected to improve the financial and non-financial performance of UMKM. The exhibition stand, which was held as part of the Real Work Lecture work program for University of North Sumatra students, is expected to be able to promote natural cassava products from Desa Perkebunan Tanjung Kasau with the brand U.K.K3: Cassava Karya Kita Kita. The aim is to revive the economy, increase buyer interest, sales figures and inseparable from getting profits, by adding product value in promotions.